2017
DOI: 10.12793/tcp.2017.25.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of healthy human urine following administration of glimepiride using a liquid chromatography-tandem mass spectrometry

Abstract: Glimepiride, a third generation sulfonylurea, is an antihyperglycemic agent widely used to treat type 2 diabetes mellitus. In this study, an untargeted urinary metabolomic analysis was performed to identify endogenous metabolites affected by glimepiride administration. Urine samples of twelve healthy male volunteers were collected before and after administration of 2 mg glimepiride. These samples were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS), and then subjected to multivariate data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…To date, metabolomics-based approaches have become increasingly applied to all aspects of diabetes research. Recent literature shows that metabolomics has been applied to biomarker and drug discovery, drug assessment [259, 260], toxicology [261, 262], and clinical biochemistry with a particular focus on gestational diabetes mellitus (GDM) [263270]. Some of the recent metabolomics-aided discoveries in antidiabetic plant research are summarised below.…”
Section: Metabolite Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, metabolomics-based approaches have become increasingly applied to all aspects of diabetes research. Recent literature shows that metabolomics has been applied to biomarker and drug discovery, drug assessment [259, 260], toxicology [261, 262], and clinical biochemistry with a particular focus on gestational diabetes mellitus (GDM) [263270]. Some of the recent metabolomics-aided discoveries in antidiabetic plant research are summarised below.…”
Section: Metabolite Profilingmentioning
confidence: 99%
“…An LC–MS n -based profiling of urine samples showed that the sulfonylurea drug glimepiride caused a reduction in the levels of cyclic adenosine monophosphate (cAMP) in urine indicating that glimepiride affects cAMP. cAMP is a secondary messenger important for insulin secretion as well as the metabolism of the amino acids: purine, tyrosine and histidine [259]. This suggested that cAMP can be a potential target for anti-diabetic therapy, and that protein metabolism abnormalities can be expected as a side-effect of glimepiride.…”
Section: Metabolite Profilingmentioning
confidence: 99%
“…PLS-DA attempts for optimal break-down of predictor variable X to best explain the response variable Y [73,78,79]. An upgraded version of PLS-DA called OPLS-DA ("orthogonal" PLS-DA) has also gained popularity [80][81][82][83][84]. This model recapitulates the variance into parts that are predictive of the experimental groups and parts that are purely due to noise, also referred to as 'orthogonal' [85][86][87].…”
Section: Methodsmentioning
confidence: 99%
“…Several endogenous metabolites, such as UCA, were found to change between pre‐ and posturine samples. The data suggested that the pharmacometabolomic approach using LC‐MS/MS was useful to understand the biochemical changes caused by glimepiride use [47].…”
Section: Analytical Techniquesmentioning
confidence: 99%